A review of Ghana’s planting for food and jobs program: Implementation, impacts, benefits, and costs - Pauw, Karl (Springer, 2022)
Farm input subsidies are widely used in Sub-Saharan African countries as a response to low adoption of fertilizers and seeds. While subsidy programs traditionally focused on helping farmers access inputs, new generation market smart subsidies additionally emphasize careful targeting, development of input supply systems, and complementary production and marketing support mechanisms. Ghana’s Planting for Food and Jobs (PFJ) initiative, launched in 2017, is one example of such an evolved subsidy program; yet, despite its scale and prominence, the current government monitoring and evaluation system is not well equipped to accurately assess its impacts. This paper triangulates evidence from multiple public sources and independent evaluations to develop a simple and effective impact assessment model for PFJ that can easily be adopted by the government. It can also be adapted to other contexts with minimal adjustment. Model results reveal that maize and rice production levels are more than 40 percent higher than they would have been in the absence of PFJ, thus contributing significantly to food and calorie availability in Ghana. However, there is much room for efficiency improvements that would increase the return on investment-currently, program benefits roughly equal public and private costs of the program. In this regard, several recommendations are made relating to beneficiary targeting, crowding out of commercial input sales, input use efficiency, marketing support to farmers, and improvements in the monitoring and evaluation system, all of which have relevance for other countries implementing or considering similar programs.